Clinicopathological Analysis of B Cell Lymphomas, Unclassifiable; with Features Intermediate Between Diffuse Large B-Cell Lymphoma and Burkitt Lymphoma in a Tertiary Care Hospital in Southern India - Selvi, Subramanian Kalaivani (Indian J Hematol Blood Transfus, 2015)
B-cell lymphomas, unclassifiable; with features intermediate between large B-cell lymphoma and Burkitt lymphoma (BCLu-DLBCL/BL) is a new entity included in the recent World Health Organization (WHO) classification of Tumours of the Hematopoietic and Lymphoid Tissues (2008) to overcome the problems of difficulty in classifying certain lymphomas having overlapping morphological, immunophenotypical and genetic features. To study the clinicopathological profile of BCLu-DLBCL/BL. Cross-sectional study over 3 year period in the Haematology section of Department of Pathology in a large teaching hospital in Southern India from January 2011 to December 2013. All the cases reported as BCLu-DLBCL/BL were collected and the clinical, morphological and immunohistochemical parameters were analyzed. Descriptive statistics. There were seven cases, four males and three females, of age ranging from 20 to 70 years. Five cases had extranodal involvement. Four cases had Burkitt morphology with strong Bcl2 positivity and absent CD10 expression. One case had the morphology and immunophenotype that of typical BL, along with strong positivity to Bcl2 suggesting a double hit hypothesis. Two cases had morphology and immunophenotype of BL with low Ki 67. Three patients on follow up had adverse outcome. BCLu-DLBCL/BL, a provisional category in WHO 2008 is useful in classifying the cases not meeting the criteria for classical BL or DLBCL. Each of these cases was interesting with different sites of involvement, different morphological features and immunophenotype with most of the patients on follow up ending with a grave prognosis.